Treatment of Chronic Typhoid Carriers with Ampicillin - Johnson, Warren D. (1973)
Ten chronic enteric typhoid carriers treated with oral ampicillin have been followed for 4 to 9 years and no relapses have occurred. Patients are probably cured if relapse does not occur within 2 years.